Pendampingan Penyampaian Character Building Untuk Siswa SMP di Masa Pandemi - Felik Sad Windu Wisnu Broto; Soetam Rizky Wicaksono; Melany Agustina (LPPM Universitas Trunojoyo Madura, 2021)
The pandemic period caused learning to take place online, so the delivery of character building (CB) in accordance with the school's mission, especially at SMPK Santa Maria I became more difficult for teachers. So that the community service team, with the support of the school principal, organized a CB delivery activity which included a mentoring process for teachers to create CB modules and webinar activities for all students which were divided per class 7, 8 and 9. After the activity was completed, an evaluation was carried out by a team of teachers appointed and it was reported that the level of student discipline in online learning had increased, and the motivation to learn and also the level of student motivation also experienced the same. However, the evaluation that is not well documented has become an obstacle in the implementation of the evaluation.